Analysis and Research on the Effect of Rosenthal Effect on College Students' Volleyball Training (Asian Journal of Social Science Studies, 2022)
In this study, 40 undergraduates from Ludong university were selected as the research sample, and the methods of documentation, experiment and mathematical statistics were used to carry out the normal training by rosenthal effect groups, it was found that the students trained by the rosenthal effect was higher than that of the students not trained by the rosenthal effect. Not only could the atmosphere of the volleyball training be harmonized, but also the training effect was good, this shows that the rosenthal effect plays an important role in volleyball training.